A inclusão de crianças com dificuldades de aprendizagem com a utilização de jogos e brincadeiras - Sousa, Ana Karolynne Pereira (Universidade Federal do Tocantins, 2023)
The purpose of this monograph is to discuss children with learning difficulties inclusion through the use of games and plays. It discusses the theme of application of games to teach abstract concepts, seeking to promote the inclusion of children with disadvantages in the acquisition of the minimum knowledge required by the regular school. The field observation as well as the performance of the internship activities, object of the present reflections, was carried out in a school of municipal education network in the city of Miracema do Tocantins - TO. In this perspective, the central objective of this monograph is to understand the importance of games for teaching skills and competences in the early years of Elementary School, articulating this pedagogical strategy to the inclusion of children with learning difficulties. In order to deepen this theme and to face some of the doubts that concern many of the educators, the following questions were raised: In the practice of the common teaching classes of a school there is space to promote the inclusion of children who have difficulties to meet expectations of learning? What pedagogical strategies can help children with learning difficulties? How to favor an education for all despite all the diversity that we find in the daily life of a classroom? These questions led us to the hypothesis that the use of games and play could be an important resource both for the teacher who can plan cognitive challenges that generate interest and curiosity and for children who are involved in play, including those who have some kind of difficulty in learning. learning. Games and games challenge children to face their difficulties in a playful way by learning and progressively developing the expected skills and competences. As the maxim “who plays more learns more” states that we assume the creative potential of children as support for a more fun and dynamic learning, consolidating the acquisition of new knowledge in such a relevant stage of human development: childhood.